Single Institutional Experience of Stereotactic Radiosurgery Alone for First Brain Metastatic Event and Salvage of Second Brain Metastatic Event in a Community Setting with Review of the Literature - Ahmad, Shaharyar; Ricco, Anthony; Brown, Royce; Hanlon, Alexandra; Yang, Jun; Feng, Jing; Stanley, Michael; Buonocore, Richard; Okpaku, Aubrey; Arrigo, Steven; Lamond, John; Brady, Luther; et al. (Frontiers in Oncology, 2017)
PURPOSE: To document survival for patients treated with SRS alone for brain metastases either at initial presentation or for salvage in conjunction with other known prognostic factors in a single institutional community setting with comparison to current literature. METHODS: All patients treated for brain metastases with SRS between October 2006 and October 2013 were reviewed. We identified 91 patients treated with SRS alone for first brain metastatic event (FBME) and 87 patients treated with SRS for second brain metastatic event (SBME). We excluded the 14 patients from each group to satisfy the independence assumption for comparison of groups. Patient demographics including age, gender, primary cancer type, presence of extracranial metastases, number of brain metastases, initial site of metastases (brain vs. other), Recursive partitioning analysis (RPA) and Karnofsky Performance status (KPS) were documented. RESULTS: There were no significant differences in overall survival for patients treated with SRS for FBME compared with SBME (log-rank p=0.9347). Univariate and multivariable Cox regression modeling revealed KPS (p=0.0003) and RPA (p=0.0143) were the only independent prognostic factors for survival. Specifically, patients with RPA 1 had a 61% decreased risk of death compared to those with RPA 3. Patients with RPA 2 had a 33% decreased risk of death compared to those with RPA 3. The 1-year survival rate was 36.5% for patients with RPA1, 33.3% for those with RPA 2, and 17.1% for those with RPA 3. Patients with KPS 90-100 had a 62% decreased risk of death compared to those with KPS <70. The 1-year survival rate for patients KPS 90-100, 70-80, <70 were 60.7%, 24.6%, and 16.7%, respectively. CONCLUSIONS: No difference in survival was noted for FBME and SBME with performance status the single most important prognostic factor following SRS. Aggressive treatment should be considered for patients with good performance status regardless if presenting with FBME or SBME. Our results are consistent with single, multi-institutional and randomized trials after literature review.